A comparative pharmacokinetic study of DRL_BZ, a candidate biosimilar of bevacizumab, with Avastin® (EU and US) in healthy male subjects - Wynne, Chris; Schwabe, Christian; Batra, Sonica Sachdeva; Lopez‐Lazaro, Luis; Kankanwadi, Suresh (British journal of clinical pharmacology, 2018)
Aim The aim of this study was to compare the pharmacokinetics (PK) of DRL_BZ with that of EU‐approved (reference medicinal product; RMP) and US‐licensed (reference product; RP) bevacizumab (Avastin®) in healthy male subjects. Methods In this double‐blind, parallel‐group, Phase 1 study (BZ‐01‐001), men aged 20–45 years were randomized 1:1:1 to receive a single intravenous infusion of 1 mg kg−1 of bevacizumab as DRL_BZ, RMP or RP. A total of 149 subjects were randomized (DRL_BZ, 50; RMP, 50; RP, 49). Primary endpoints included maximum observed serum concentration (Cmax), area under the concentration–time curve from time zero (pre‐dose) extrapolated to infinity (AUC(0–∞)), and area under the concentration–time curve from time zero (pre‐dose) to last quantifiable concentration (AUC(0–t)). Secondary objectives were to compare the safety and immunogenicity of DRL_BZ with those of the reference products. Results Primary PK parameters were comparable across groups, and 90% confidence intervals for the geometric mean ratios of the primary PK endpoints were within the pre‐specified equivalence margins (80–125%) for all pairwise comparisons (DRL_BZ vs. RMP, DRL_BZ vs. RP and RMP vs. RP). No deaths or serious adverse events were reported. Similar numbers of subjects reported similar numbers of treatment‐emergent adverse events in the three treatment groups. One subject who received DRL_BZ had anti‐drug antibodies at the Day 85 visit; however, no anti‐drug antibodies were detected in this subject at the 12‐month follow‐up visit. Conclusions PK, safety and immunogenicity of DRL_BZ were comparable to EU‐approved and US‐licensed bevacizumab in healthy male subjects.